ANALISIS INDEKS NILAI PENTING HUTAN MANGROVE BULALO GORONTALO UTARA - Ernikawati, Ernikawati; Sandalayuk, Daud (MAKILA, 2024)
Importance Value Index (INP) analysis can be used to determine which species dominates the observation plot. A species that can utilize its environment more than other species in an area is said to be dominant. The critical value index represents the many mangrove species contributing to the ecosystem. Certain mangrove species are essential and have an impact on mangrove communities. This research aims to analyze the Importance Value Index of the Bulalo mangrove. The method used in this research is using the Double Plot Path. The research results show that the Important Value Index (INP), relative cover (RCi), relative frequency (RFi), and relative density values (RDi) are generally classified as good. Based on the Importance Value Index (INP), mangrove vegetation has a reasonably high role in protecting the coastal environment in the coastal area of Bulalo Village, both in terms of tree saplings and seedlings.